2021
DOI: 10.1002/qre.2887
|View full text |Cite
|
Sign up to set email alerts
|

On the multivariate progressive control chart for effective monitoring of covariance matrix

Abstract: With the development of modern acquisition techniques, data with several correlated quality characteristics are increasingly accessible. Thus, multivariate control charts can be employed to detect changes in the process. This study proposes two multivariate control charts for monitoring process variability (MPVC) using a progressive approach. First, when the process parameters are known, the performance of the MPVC charts is compared with some multivariate dispersion schemes. The results showed that the propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Finally, several issues are recommended for future studies of the THWMAV charts. For example, the concepts of the THWMAV charts can be used with the idea of neutrosophic statistics [32,33], in the high-yield processes [34], in multivariate process cases [35], etc.…”
Section: Summary Conclusion and Recommendationsmentioning
confidence: 99%
“…Finally, several issues are recommended for future studies of the THWMAV charts. For example, the concepts of the THWMAV charts can be used with the idea of neutrosophic statistics [32,33], in the high-yield processes [34], in multivariate process cases [35], etc.…”
Section: Summary Conclusion and Recommendationsmentioning
confidence: 99%
“…is study is carried out where the process variable follows the univariate distributions. However, the proposed NPDHWMA RSS charting scheme can be used to enhance the monitoring of high-quality processes [29,30], time-between-events [31], multivariate processes [32], and neutrosophic statistics [33,34] scenarios. Data Availability e data used in the real-life application can be obtained from the corresponding author upon request.…”
Section: Summary Conclusion and Future Recommendationsmentioning
confidence: 99%
“…Some recent modifications/extensions of PM chart can be seen in Abbasi et al 5 . Ajadi et al., 6 Alevizakos and Koukouvinos, 7 Mahmood et al 8 . and references therein.…”
Section: Introductionmentioning
confidence: 99%
“…respectively. Some recent modifications/extensions of PM chart can be seen in Abbasi et al 5 Ajadi et al, 6 Alevizakos and Koukouvinos, 7 Mahmood et al 8 and references therein. Through some mathematical manipulations, Abbas 1 showed that the PM statistic in (2) can be rewritten as:…”
Section: Introductionmentioning
confidence: 99%